Overexpression of Trigger Factor Prevents Aggregation of Recombinant Proteins in Escherichia coli - Nishihara, Kazuyo (American Society for Microbiology, 2000)
To examine the effects of overexpression of trigger factor (TF) on recombinant proteins produced in Escherichia coli, we constructed plasmids that permitted controlled expression of TF alone or together with the GroEL-GroES chaperones. The following three proteins that are prone to aggregation were tested as targets: mouse endostatin, human oxygen-regulated protein ORP150, and human lysozyme. The results revealed that TF overexpression had marked effects on the production of these proteins in soluble forms, presumably through facilitating correct folding. Whereas overexpression of TF alone was sufficient to prevent aggregation of endostatin, overexpression of TF together with GroEL-GroES was more effective for ORP150 and lysozyme, suggesting that TF and GroEL-GroES play synergistic roles in vivo. Although coexpression of the DnaK-DnaJ-GrpE chaperones was also effective for endostatin and ORP150, coexpression of TF and GroEL-GroES was more effective for lysozyme. These results attest to the usefulness of the present expression plasmids for improving protein production in E. coli.